Zróżnicowanie zjawiska zarobkowych migracji zagranicznych ludności wiejskiej - Perepeczko, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
Huge surplus of labour force and the lack of satisfactory incomes cause rural population to searching for earnings in foreign countries. The dynamics of international economic migrations of rural population is significant and became the form of income diversity. The scale, structure and impacts of that complex and regionally diverse phenomenon are very hard to catch, which is probably the reason of weak interest of economists. On the basis of sociological research conducted in three villages from the regions of the highest intensity of international migration the author states that international migrations from the village situated in Opolskie are more often the choice and fixed strategy of rural families, migrations from the village situated in Podlasie are more often necessity caused by weakness of local labour market and worse human capital of villagers and worse material situation of families. People from villages of Podkarpackie, who work abroad, with regard to non-agricultural qualifications and increase of chances of getting better paid jobs can choose return and reverse tendency of migrations from that region